Determinants of tax audit quality with audit process as the mediator in Ethiopia: the case of the ministry of revenues / Shemelis Zewdie Mersha, Amsalu Bedemo Belaye and Lemessa Bayissa Gobena - Mersha, Shemelis Zewdie; Belaye, Amsalu Bedemo; Gobena, Lemessa Bayissa (Universiti Teknologi MARA, 2022)
This study analyzed the determinants of tax audit quality with the audit process as the mediator in Ethiopia with special reference to the Ministry of Revenues. A mixed research approach with concurrent triangulation was used in the study. The conceptual model was developed based on the Agency Theory, Contingency Theory, Inspired Confidence Theory, Stakeholder Theory, and an empirical literature review. The data was collected from tax auditors including tax directors, supervisors, process owners, and team leaders using a questionnaire survey and key informant interviews. Thematic analysis and PLS-SEM using the ADANCO were used to analyze the qualitative and quantitative data respectively. The findings revealed that audit input factors, audit process, and contextual factors had a positive significant effect on tax audit quality. In addition, the audit process had a mediation effect on the relationship between explanatory variables in this study and tax audit quality.